Improving the perception of urban space for women by emphasizing the use of new technologies from the perspective of future studies - Fatemeh Khodadadi Aghghaleh; Mohammadreza Akbarian (مهندسی و مدیریت ساخت)
Future studies is looking at the future at different levels in order to better understand the changes between humans, society and their environment. Due to new technologies, urban spaces have taken on a different process of understanding and experience. The perception of space is the first step in establishing a person's relationship with the environment, and this recognition causes the formation of a mental image and, as a result, the creation of a cognitive map of the space. It is in the mind. The purpose of this research is to investigate the impact of new technologies as one of the forward-looking tools in improving the perception of urban space for women. The main question here is whether it is possible to define indicators for the recognition and application of new technologies in order to improve spatial perception for women with a future research approach. In dealing with any space, the human mind limits and makes the space perceptible by placing an index element in it. Obviously, the perception of space is a higher level of the sense of place, which plays a decisive role in order to benefit and continue human presence in the place. Meanwhile, preparing to face the future in a rapidly changing world is one of the necessities of every society. Most researchers and theorists believe that the smartest way to face the future is to prepare for it; In today's era, the perception of space is formed not only through sensory involvement with the place, but also by accessing the information layer and awareness of data, and the virtual experiences of people to the place. Therefore, the investigation of new technologies by the cognitive map of people, can be an effective step in the direction of women's perception of the urban space.